Moisture damage in asphalt mixtures: A review of the causes, testing, and mitigating methods (Advances in Civil and Architectural Engineering, 2025)
The early 1900s saw the commencement of the production and utilization of asphalt mixtures for road paving. Asphalt pavements carry heavy repetitive traffic loads under extreme environmental conditions over their service life. Several issues and defects have emerged, resulting in highway deterioration and failure. One of the main reasons for asphalt pavement failure is moisture damage, and poor rainwater drainage, with the associated accumulation of water on the pavement surface, can exacerbate the consequences. Moisture damage in asphalt pavements refers to the reduction in stiffness and shortened lifespan owing to a lack of adhesion between the bitumen and aggregate or rupturing of the bitumen. This study consists of several sections: a comprehensive review of the concepts, theories, and causes of moisture damage in asphalt mixtures; a discussion of the factors contributing to damage; and a survey of the laboratory testing procedures used to assess the durability of asphalt mixtures against moisture effects. Several methods that focus on developing and strengthening asphalt mixtures to withstand the adverse impact of water are discussed. The study's main conclusion is that poor bitumen–aggregate adhesion is the primary cause of moisture damage in asphalt mixtures. Several laboratory techniques aid in assessing this damage, but each has limitations. To increase moisture resistance, several methods are suggested, including mix design optimization and fibre, polymer treatment, and additive utilization. The most important finding of the study is that mixing various modifiers may be economically beneficial in moisture damage resistance.